Strength and conditioning for track and field. Throws - Stone, M. (Strength and conditioning for sports performance, 2016)
When considering the characteristics essential to the throwing events in track and field, through simple observation and in-depth research, it is evident throwers are amongst the strongest and most explosive athletes in the world of sport. Therefore, in designing a training programme for throwers, these specific characteristics must be addressed and enhanced if the thrower is to reach his/her genetic potential. Designing a training programme for any sport requires an understanding of how the components ot the programme integrate. Testing, evaluating, planning and monitoring the training programme are essential elements of the training process if the athlete`s progress is to be tracked and recorded and ultimately to lead to successful performances. However, testing, monitoring and evaluation are beyond the scope of this chapter, and the planning of the training process will remain the primary focus. Other parameters such as nutrition, medical examinations, sport psychology integration and biomecbanical analysis must be addressed in the integrated training programme and as part of the annual and quadrennial plan. What are the physical characteristics a thrower needs to develop in order to successfully compete in the sport of track and field? The most important characteristics to develop are absolute strength and explosiveness. In working with the developmental thrower it is essential to lay a foundation of strength while developing sound throwing mechanics. Later, alter a base of strength has been developed and only then should power development become a primary objective. The following stages of physical development can be suggested for the developing thrower. It must be noted that in order to develop the strength levels necessary to throw at the elite level the athlete may need to spend a great deal of time revisiting training periods devoted to basic strength, even after introducing blocks of training involying power development. Two periods of training will be discussed, using two 20-week (macrocycle) periods with five blocks of training each containing 4 week training blocks (mesocycle). When these training blocks are performed in sequence they are referred to as summated mesocycles. The first 20 weeks are focused on strength development, and the second 20 weeks on power development.